Steps
1.
So with this system, I will be using the substitution method. Since we know that y = 6x - 6, substitute y in the second equation for 6x - 6 and solve for x as such:
![2x+2(6x-6)=2\\2x+12x-12=2\\14x-12=2\\14x=14\\x=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ve3ef8cy4x6f926i71xjyw1tg3074ccr4g.png)
Since we know the value of x is 1, substitute it into either equation to solve for y:
![y=6*1-6\\y=6-6\\y=0\\\\2*1+2y=2\\2+2y=2\\2y=0\\y=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/493rzbb5q1bl8s1hz15xu79ppoyad4w56l.png)
In the form of (x,y), the answer is (1,0).
2.
For this system, I will also be using the substitution method. Since we know that y = -3x + 5, substitute that into the second equation to solve for x as such:
![5x-4(-3x+5)=-3\\5x+12x-20=-3\\17x-20=-3\\17x=17\\x=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cy9n9ah1adz2tuckb3t42bii3kqfcoi3c7.png)
Since we know that the value of x is 1, substitute it into either equation to solve for y:
![y=-3*1+5\\y=-3+5\\y=2\\\\5*1-4y=-3\\5-4y=-3\\-4y=-8\\y=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8opjd51dpa2iigz039w1kuahejv8a1bfpp.png)
In (x,y) form, the answer is (1,2).
Answers
In short:
- (1,0)
- (1,2)